154k views
11 votes
3b^2-19b+1=-5
Solve the quadratic equation using the technique of factoring

User Tvashtar
by
4.7k points

1 Answer

10 votes

Answer:


6 \: or \: (1)/(3)

Explanation:


3b {}^(2) - 19b + 1 = - 5 \\ 3b {}^(2) - 19b + 1 + 5 = 0 \\ 3b {}^(2) - 19b + 6 = 0 \\ 3b {}^(2) - b - 18b + 6 = 0 \\ b(3b - 1) - 6(3b - 1) = 0\\ (b - 6)(3b - 1) = 0 \\ b = 6 \: or \: 3b = 1 \\ b = 6 \: orb = (1)/(3)

User Jamesernator
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.